Steganography based on parameters’ disturbance of spatial image transform - Xi SUN; Wei-ming ZHANG; Neng-hai YU; Yao WEI (Tongxin xuebao)
In the research of state-of-the-art steganography algorithms,most of image sources were natural images in laboratory environment.However,with the rapid development of image process tools and applications,images after image processing were widely used in real world.How to use image process to improve steganography has not been systematically studied.Taking spatial image transform for consideration,a parameters’ disturbance model was presented,which could hide the noise taken by steganography in the pixel fluctuation due to the disturbance.Meanwhile,it would introduce cover source mismatch for a steganalyzer.The experimental results show that,compared with using traditional image database,it can significantly enhance the security of steganography algorithms and accommodative to the real world situation.